Zemiology Reconnecting Crime and Social Harm (Critical Criminological Perspectives, 2018)
This book challenges the given dichotomies between crime and harm, and criminology and zemiology. The main aim of the volume is to highlight the inexorable interconnectedness between systemically induced social harm and the corrosive flows of everyday crime both perpetrated and endured by those victimised by the capitalist system and its hegemonic vicissitudes. Drawing attention not only to various structurally imbedded harms, the chapters also outline the wider consequences of such harms, as they extend beyond immediate victims and contribute towards the further perpetuation of criminogenic and zemiogenic conditions. Comprising two parts, the first explores the relationship between crime and harm and criminology and zemiology, and the second explores the intersections of crime and harm through various lenses, including those trained on probation; global mobility; sexuality and gender; war and gendered violence; fashion counterfeiting; and the harms of the service economy. An exciting and wide-reaching volume written by world-renowned scholars, this collection is a must-read for students, academics, and policy makers in the fields of law, criminology, sociology, social policy, criminal justice, and social justice.